Pengaruh Penerimaan Diri terhadap Body Image Siswa SMA - Saputri, Valentina Beta Mei; Setiawan, Antonius Ian Bayu (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2025)
The purpose of this study was to identify the level of self-acceptance and body image of high school students and to identify the effect of self-acceptance on students' body image. This study used quantitative descriptive correlation research with subjects of class X students of SMA Stella Duce 1 Yogyakarta. The sample in this study was 173 students. The analysis techniques in this study included categorization, validity test, reliability test, normality test, linearity test and linear regression hypothesis test. Data collection used a body image and self-acceptance scale. On the body image scale there were 22 valid items and on the self-acceptance scale there were 25 valid items. The results of the reliability test on the body image and self-acceptance scales obtained an Alpha Cronbach reliability index of 0.891. Hypothesis testing in this study used ANOVA linear regression. Based from research, there is a significant relationship between self-acceptance and student’s body image because the magnitude of the correlation value (R) is 0.634 with a significance level of 0.001b. The level of significance is 0.001b < 0.05, which indicates that there is an influence between the body image variable and the self-acceptance variable in high school students.